The Implementation of Think Pair Share Model to Improve Mathematical Communication Ability on MTs Students - Syaprila, Alma Amaliana; Amelia, Risma (IKIP Siliwangi, 2025)
Mathematical communication ability is a crucial aspect of mathematics learning, as it enables students to express ideas, understand concepts, and solve problems systematically. This study aims to analyze the implementation of the Think Pair Share (TPS) learning model on students mathematical communication skills at Madrasah Tsanawiyah (MTs) level. The research method used is a Mixed Method with an Explanatory Sequential Design. The sample consisted of two classes: the experimental class, which used the Think Pair Share model, and the control class, which used a conventional learning model.The results showed that the mathematical communication skills of MTs students taught using the Think Pair Share model were better than those taught using a conventional model. The N-gain results also indicated that the improvement in communication skills was greater in the Think Pair Share group. This was supported by student statements in interviews, indicating that the Think Pair Share (TPS) model made learning more enjoyable and allowed more freedom in thinking, discussing, and expressing solutions. This contributed to increased communication abilities. Based on the findings, it can be concluded that the implementation of the Think Pair Share learning model results in a statistically significant improvement in students' performance compared to the conventional learning model. Accordingly, the Think Pair Share model may serve as an effective pedagogical alternative for enhancing mathematical communication skills among students at the Madrasah Tsanawiyah (MTs) level. The implementation of this model is expected to be integrated into mathematics instruction as a means of enhancing students communication skills.